High yielding ridge gourd F1 hybrid from KAU - Kumar, T Pradeep; Aswini, A (Indian Horticulture, 2020)
Ridge gourd F1 hybrids were developed at Kerala Agricultural University, Trichur exploiting cytoplasmic genic male sterility (CGMS) system. Hybrid, KRH- 1 is a cross between male sterile female line (KAU-MS-LA 101) and male fertile male line LA-102. It has proved to be highly heterotic with a high yield (7.419 kg/plant) bearing attractive long slender fruits. Hybrid KRH-1 is male fertile and produces more number fruits. Hybrid MS Ã— LA 102 is male fertile and superior in terms of total yield (7.386 kg/plant) when compared to other parents and hybrids.